Вплив радянської ідеології на археологічні дослідження в Ольвійській експедиції в середині 30-х років XX ст. - Каряка, О.В. (Археологія і давня історія України, 2017)
Стаття присвячена висвітленню маловідомих
сторінок з історії організації досліджень античного міста Ольвія Понтійська на півдні України в 1930-і роки. В статье рассматриваются малоизвестные страницы из истории организации исследований античного города Ольвия Понтийская на юге Украины.
Смена поколений исследователей в тридцатые годы
XX в. была переломным моментом в истории формирования отечественной археологии. Возобновление
археологических исследований на территории Ольвии Понтийской в 1935 г. под руководством Ф. А. Козубовского стало последней попыткой создания национальной школы античной археологии в Украине
в предвоенный период. Во время этих раскопок была
предпринята попытка создания археологической экспедиции нового социалистического образца. Многие черты в работе Ольвийской экспедиции этого года стали традиционными и в советский период, а некоторые существуют и в настоящее время. This article is devoted to the revelation of unknown
pages of the history of investigations of the classical city
Olbia Pontica of the South of the Ukraine. The period
of 30th years of the XX c. was a critical moment in the
history of forming of the Ukrainian archaeology. Renewal
of the excavations of the territory of Olbia Pontica
in 1935 under the leadership of F. A. Kozubovskij
became the last attempt of the creation of the national classical school of archaeology in the Ukraine in the
prewar period. The attempt of the creation of a new socialist model of archaeological expedition was realized
in these excavations. A lot of features of the work of this Olbian expedition of this year became traditional
in the soviet period and some of them are stable in the present time.